The Impact of the Institution on Economic Growth: An Evidence from ASEAN - Vita Kartika Sari; Dwi Prastyani (Department of Development Economics, Universitas Sriwijaya, 2021)
The ideal community life structure has a strong institutional level. Economists agree on the institution as an important factor in creating economic growth. The purpose of this study was to investigate the influence of institutional factors on economic growth in ASEAN. Institutional variables include political stability, voice and accountability, government effectiveness, regulatory quality, rule of law, and control of corruption, while economic variables include exports and imports. This study utilized panel data estimation on 10 countries in ASEAN during 2002-2018. The fixed effect model was the best estimation model. The findings show that there are three keys of institutions that had a significant influence on per capita GDP on ASEAN, namely voice and accountability, regulatory quality, and rule of law. It could be that if the institutional factors are weak, it will be detrimental to economic performance. The policy implication is that the synergy of all stakeholders needs to be improved for better institutional enforcement.